Development and validation of a new LC-MS/MS method for the determination of orlistat in biological matrices using experimental design - Rubina Kauser, Sunil Kumar Chaitanya Padavala, Venkatesan Palanivel (Journal of Applied Pharmaceutical Science, 2024)
The primary objective of this study was to develop a sensitive tandem mass spectrometric technique for the quantitative determination of Orlistat in biological matrices by combining electrospray ionization with liquid chromatography. To accomplish chromatographic elution at a flow rate of 0.80 ml/minute, a stationary Phenomenex-C18 column (2.1 mm × 50 mm, 5μ) was utilized. A mobile phasic system consisting of methanol, acetonitrile, and 0.1% formic acid was used for isocratic elution in a ratio of 65:20:15 V/V/V. A 5 ml of ethyl acetate was used as a solvent for the liquid-liquid extraction that separated the drug and internal standard. On repeated reaction monitoring, the Orlistat’s parent and product ions were observed at m/z 496.4/142.08, while the Orlistat-D5 internal standard was detected at m/z 501.3/147.07. Rectilinearity and a r2 value of 0.9999 were seen in the drug’s linearity graph at doses ranging from 1.2 to 392.0 ng/ml. Values for the relative standard deviation of accuracy % between batches varied from 2.84 to 5.32. Results for the lower quality control (LQC) sample were 103.62%, the medium quality control (MQC) sample was 96.14%, and the high-quality control (HQC) sample was 95.73%. The recoveries from this strategy were outstanding. Stability studies were conducted under various conditions, and the results showed stability values between 93.19% and 103.47%. Orlistat remains more stable under different stability settings for a longer period, and the method was found to be useful for routinely analyzing Orlistat in biological materials.
Keywords: Orlistat, Type-2 diabetes, LC-MS/MS, USFDA guidelines, stability, linearity